2019
DOI: 10.1186/s12885-019-5288-y
|View full text |Cite
|
Sign up to set email alerts
|

The JNK signaling pathway plays a key role in methuosis (non-apoptotic cell death) induced by MOMIPP in glioblastoma

Abstract: BackgroundSynthetic indolyl- pyridinyl- propenones (IPPs) induce methuosis, a form of non-apoptotic cell death, in glioblastoma and other cancer cell lines. Methuosis is characterized by accumulation of cytoplasmic vacuoles derived from macropinosomes and late endosomes, followed by metabolic failure and rupture of the plasma membrane. However, not all IPPs that cause vacuolization are cytotoxic. The main goals of the present study were to identify key signaling pathways that contribute to methuosis induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…Thus PFKFB3 inhibition can trigger methuosis along with apoptosis in MPM. Remarkably, a very recent study revealed that chalcones, known to be methuosis inducers, also can adversely interfere with glucose uptake 36 . We are the first to show a metabolic connection between glycolysis with elevated macropinocytosis and impaired lysosomal function to induce methuosis and reveal a crucial role of glucose metabolism in maintaining nutrient and energy homeostasis to sustain cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus PFKFB3 inhibition can trigger methuosis along with apoptosis in MPM. Remarkably, a very recent study revealed that chalcones, known to be methuosis inducers, also can adversely interfere with glucose uptake 36 . We are the first to show a metabolic connection between glycolysis with elevated macropinocytosis and impaired lysosomal function to induce methuosis and reveal a crucial role of glucose metabolism in maintaining nutrient and energy homeostasis to sustain cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol and MOMIPP have been proven to cross the BBB [35,74,75]. Although vacquinol-1 also displays an adequate BBB penetration, its systemic toxicity requires a lowering dose or local delivery [76].…”
Section: Discussionmentioning
confidence: 99%
“…Both honokiol and MOMIPP have been shown to kill drug-sensitive and -resistant glioma cells [29,77]. Recent studies pointed JNK Kinase as an important signal for both honokiol-induced effects on stem cells [78] and cytotoxic effects of indoylchalcones such as MOMIPP [75].…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that different mechanisms of action were responsible for the differences in response to 10 µmol/l and ≥20 µmol/l TetC treatment. In the 10 µmol/l TetC-treated group, cell vacuolization was an indication of mitochondrial or endoplasmic reticulum denaturation (32), although some researchers consider this to be the result of methuosis (33). In the 20 and 40 µmol/l TetC-treated groups, cell rounding was more likely to be associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%